Leadership In Action : a Question of Leadership - What Are the Biggest Challenges Faced by Leaders who manage a Global Organization with an International Workforce? - Knudson, Thomas C. (Center for Creative Leadership, 2002)
Global leaders need a sound grasp of the three C's: context, content, and creativity.